Symmetrical peripheral gangrene: potential mechanisms and therapeutic approaches in severe COVID-19 - Wang, Manzhi; Sun, Tao; Dong, Liang; Huang, Shengshi; Liu, Ju (Frontiers in Cardiovascular Medicine, 2023)
Symmetrical peripheral gangrene is a rare condition that is characterized by ischemic damage and tissue death (gangrene) in the extremities. Recent reports have shed light on SPG in patients with severe COVID-19. This condition presents with symmetrical cyanosis of the extremities and common COVID-19 symptoms and what the most frightening is within a few days, cutaneous necrosis occurred and patients died. Skin biopsy results have shown the presence of microthrombi in small vessels. The formation of SPG in COVID-19 patients results from immunothrombosis, endothelial dysfunction, and procoagulant platelets, leading to a hypercoagulation state and microvascular thrombosis. Thrombotic microangiopathy, shock, disseminated intravascular coagulation, and anticoagulant depletion promote the development of SPG in COVID-19. At the early stage, SPG patients with COVID-19 exhibit similar clinical manifestations. TMA causes early damage to microvasculature in SPG, and the shock state further exacerbates the ischemic injury due to local hypo-perfusion. The disturbed procoagulant-anticoagulant balance caused by DIC and anticoagulant depletion, combined with the pre-ischemic state brought on by TMA and shock, leads to the rapid formation of extensive microthrombi in the late stage of COVID-19 associated SPG. This review will delve into the clinical features, possible mechanisms, and potential therapeutic managements for COVID-19 associated SPG.